Giant Cell Tumor: Pathogenesis and Clinical Manifestation - Adinda Ilsa Maulida; Ali Ramzi; Amrullah Muliawan H; Baiq Ghassani Kayla; Clara Nadila; Dinda Salsabila; Febbi Anggy; Herodya Lajunee Fesmia; Jihan Alifa Rahma; Trisna Ayu Kurnia Putri; Wina Aryslia Fakar; Zulfa Hasyimiyyah Ihtisyam; Nurhidayati Nurhidayati (Jurnal Biologi Tropis, 2023)
A giant cell tumor of bone (GCTB) as known as a benign bone tumor (neoplasm) is aggressive locally and frequently recurs, and it is characterized by the growth of mononuclear stromal cells and datia cells that resemble osteoclasts. GCTB has varying incidence rates and has been shown to have high mortality. GCTB patients have several treatment options, but the majority of patients still experience recurrence and even metastasis to other organs. This literature review aims to explain more deeply about Giant Cell Tumor (GCT) starting from the definition, etiology, epidemiology, pathogenesis, clinical manifestations and treatment options so that patients get a better prognosis. This literature review was conducted using the keywords "Giant Cell Tumor AND pathogenesis AND clinical manifestation" from PubMed dan Google Scholar. The results of the literature review carried out are that the molecular and biological pathogenesis of GCTB consists of 4 processes, namely tumorigenesis of neoplastic mononuclear stromal cells, generation of reactive multinucleated giant cells, bone resorption/migration, and bone matrix remodeling for angiogenesis, invasiveness, and metastasis. Besides, the histological picture of GCTB contains "reactive" osteoclasts such as multinucleated giant cells (Giant Cells/GC), round cells such as macrophages and spindle stromal cells such as "neoplastic" fibroblasts (mononuclear stromal cells/SC) which are important findings in establishing the diagnosis. In conclusion, staging and management are very important to produce a better prognosis and reduce recurrence rates in GCTB patients.